The squares 1, 25, 49 are pairwise relatively prime and in an increasing arithmetic progression. Let $x_1^2, y_1^2, z_1^2$ and $x_2^2, y_2^2, z_2^2$ be the next two triples with this property (so that 49, $z_1^2$, $z_2^2$ are the three smallest possible values of the third term). Find $z_1 + z_2$.

I really help about how to start/a good solution for this problem because I understand what the problem is asking but I'm not sure how to start. Thanks!

  • 1
    $\begingroup$ Write a system of equations. So there was no confusion in the formulation of the problem. $\endgroup$ – individ Aug 4 '17 at 13:32

First solution

Remark(1): Suppose that we can write the integer $r$ in the form $2Y^2-X^2$; then we can conclude that each prime factor of $r$; which is of the type $8k \pm 3$, must divides $r$, by an even power. In other words if $p \overset{8}{\equiv} \pm 3$ and $p^ \alpha \mid r$ and $p^ {\alpha+1} \nmid r$, then there is an integer $\beta$ such that: $\alpha=2\beta$.

Moreover in this situation every solution of $2Y^2-X^2=r$ has the form: $X=p^ \beta X^ {\prime}$, $Y=p^ \beta Y^ {\prime}$ for some integers $X^{\prime}$ and $Y^{\prime}$.

List of the prime numbers of the form $8k + 1$ are as follows:

$$17, 41, 73, 89, 97, ... \ \ \ ,$$

and the list of the prime numbers of the form $8k + 7$ are as follows:

$$7, 23, 31, 47, 71, 79, ... \ \ \ .$$

Without loss of generality we can assume that: $x_i^2 < y_i^2 < z_i^2$, so we must have $x_i^2 + z_i^2 = 2y_i^2$; so we have $z_i^2 = 2y_i^2 -x_i^2$ and $x_i^2 = 2y_i^2 -z_i^2$.

The minimum positive possible values for $(x_i,z_i)$ is equal to

$$(1,7); \ (7,17); \ (7,23); \ ... , $$

so $z_0=7$, $z_1=17$, $z_2=23$.

Second solution

Remark(2): Let's remember that a parametric solution to the equation $x^2+y^2=z^2$ is given by:

$$ \left\{ \begin{array}{lcc} x=d(m^2-n^2) \ , \\ y=d(2mn) \ , & \\ z=d(m^2+n^2) \ , \\ \end{array} \right.$$

where $m$ and $n$ are relatively prime integers with different pairity.

Remark(3): Now lets consider the equation $x^2+y^2=2z^2$; multiplying both sides by $2$ turns out: $$ (x+y)^2+(x-y)^2= 2(x^2+y^2)= 2(2z^2)= (2z)^2 . $$

Leting $x+y=d^{\prime}(m^2-n^2)$, $x-y=d^{\prime}(2mn)$ and $2z=d^{\prime}(m^2+n^2)$; and by a simple concusion we obtain the following parametric solution to the equation $x^2+y^2=2z^2$:

$$ %% \left\{ \begin{array}{lcc} %% x= \dfrac {d (m^2-n^2+2mn) }{2} %% = \dfrac {d \big( (m+n)^2-2n^2 \big) }{2} \ , %% \\ %% y= \dfrac {d (m^2-n^2-2mn)}{2} %% = \dfrac {d \big( (m-n)^2-2n^2 \big) }{2} \ , %% & %% \\ %% z= \dfrac {d(m^2+n^2)}{2} \ , %% \\ %% \end{array} %% \right.$$

$$ \left\{ \begin{array}{lcc} x= d (m^2-n^2+2mn) = d \big( (m+n)^2-2n^2 \big) \ , \\ y= d (m^2-n^2-2mn) = d \big( (m-n)^2-2n^2 \big) \ , & \\ z= d(m^2+n^2) \ , \\ \end{array} \right.$$

where $m$ and $n$ are relatively prime integers with different pairity.

So your problem reduces to minimizing the quantity $$\max \{ \ (m+n)^2-2n^2 \ , \ \ (m-n)^2-2n^2 \ \} . $$

after a simple computation you can get:

$$(m, n)=(2, 1) \rightarrow (1, 7; 5), $$

$$(m, n)=(3, 2) \rightarrow (7,17;13), $$

$$(m, n)=(4, 1) \rightarrow (7,23;17). $$

Third solution: By using the primitivity assumption, we can conclude by an easy modular arithmetic module $8$, that $r \overset{8}{\equiv} \pm 1$, so it only suffices to search thorough the integers $x_i$ and $z_i$ among the following list:

$$1, 9, 17, 25, ..., $$

$$7, 15, 23, ..., .$$

[For example note that $15$ is immpossible by lemma(1).]

  • $\begingroup$ Thank you so much! This was really helpful and I think I understand how to do the problem now. $\endgroup$ – Annie Smith Aug 4 '17 at 16:27

I noted that each triplet begins with the last number of the previous triplet

For instance $(1,5,7)$ brings to $(7,13,17)$ and then to $(17,25,31)$

Going on for a while I figured out a formula that gives all this kind of triplets:

$$\left (2 n^2-1,2 n^2+2 n+1,2 n^2+4 n+1\right)$$ Indeed $$(2 n^2+2 n+1)^2-(2n^2-1)^2=8 n^3+12 n^2+4 n$$ and $$(2n^2+4 n+1)^2-(2 n^2+2 n+1)^2=8 n^3+12 n^2+4 n$$ so squares are in arithmetic progression.

The next triplets of this kind are $(7,\;13,\;17)$ and $(17,\;25,\;31)$

  • $\begingroup$ There is an smaller solution other than $(17,25,31)$; namely $(7,17,23)$, with the sum $23+17=40$. $\endgroup$ – Davood Khajehpour Aug 4 '17 at 17:48

Famke's answer solves the problem. Still, there is indeed a direct correspondence between Pythagorean triples and your squares in arithmetic progression. [You asked about this in the original question, then alas you edited it out.]

Squares in arithmetic progression correspond to triples $d<e<f$ such that $f^2+d^2=2e^2$. And such triples correspond directly to Pythagorean triples, as follows.

a) If $f^2+d^2=2e^2$ for $d<e<f$, then $$e^2=(\frac{f-d}{2})^2 + (\frac{f+d}{2})^2$$ and we see that $\frac{f-d}{2}, \frac{f+d}{2}, e$ is a Pythagorean triple.

b) If $a^2+b^2=c^2$ for $a<b<c$ (a Pythagorean triple), then $$(b+a)^2 + (b-a)^2 = 2c^2$$ and we see that $(b-a)^2, c^2, (b+a)^2$ are squares in arithmetic progression.

So another simpler way to solve your problem is to look at the smallest three primitive Pythagorean triples $(3,4,5),(5,12,13), (8,15,17)$. These yield the required $z_0=3+4=7, z_1=5+12=17, z_2=8+15=23$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.